2009
DOI: 10.1038/nn.2401
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of nonfunctional spinal circuits into functional states after the loss of brain input

Abstract: After complete spinal cord transections that removed all supraspinal inputs in adult rats, combinations of serotonergic agonists and epidural electrical stimulation were able to acutely transform spinal networks from nonfunctional to highly functional and adaptive states as early as 1 week after injury. Using kinematics, physiological and anatomical analyses, we found that these interventions could recruit specific populations of spinal circuits, refine their control via sensory input and functionally remodel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
674
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 622 publications
(711 citation statements)
references
References 50 publications
30
674
3
4
Order By: Relevance
“…A recent study showed that epidural stimulation could effectively reactivate the lumbar motor circuitry to be more sensitive to sensory inputs provided by TMT (Harkema et al, 2011). This finding raises a hope that TMT with electrical and/or pharmacological neuromodulation could be an effective therapeutic option (Courtine et al, 2009;Edgerton and Roy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that epidural stimulation could effectively reactivate the lumbar motor circuitry to be more sensitive to sensory inputs provided by TMT (Harkema et al, 2011). This finding raises a hope that TMT with electrical and/or pharmacological neuromodulation could be an effective therapeutic option (Courtine et al, 2009;Edgerton and Roy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to regulating reflexive functions in intact animals, propriospinal neurons have also been implicated in mediating adaptive changes under pathological conditions such as spontaneous functional recovery after incomplete spinal cord injury (Bareyre et al, 2004;Courtine et al, 2008Courtine et al, , 2009Rosenzweig et al, 2010). For example, after a thoracic lateral injury, a consistent spontaneous locomotion recovery of the hindlimb on the affected side has been documented in many species.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, use-dependent mechanisms promoted the remodeling of fibers spared by the lesion 6 . Indeed, we recently showed that MSNT, an electrochemically enabled and robot-assisted rehabilitation 7 , triggered a massive reorganization of descending and intraspinal pathways in rats with severe SCI 8 . This extensive plasticity restored voluntary control over refined locomotor movements in otherwise paralyzed rats.…”
Section: Introductionmentioning
confidence: 99%